The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.5902/19805098435
|View full text |Cite
|
Sign up to set email alerts
|

Gaseificação de materiais lignocelulósicos para geração de energia elétrica.

Abstract: O objetivo deste trabalho foi construir um gaseificador contracorrente em alvenaria para avaliar o potencial de geração de energia elétrica de espécies de eucalipto cultivadas no estado de Minas Gerais, de resíduos da agroindústria e da mistura desses materiais. Determinaram-se a composição química imediata e o poder calorífico dos materiais utilizados. Experimentaram-se os diferentes materiais lignocelulósicos e a gasolina, como testemunha. Para os fatores testados, foram executadas medições dos rendimentos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…Possibly, the high level of minerals in coffee husk (Table 4) contributed to increase ash content. In the literature the ash content is reported to vary from 9 to 13.86% for coffee husk, and from 0.17 to 0.34% in Eucalyptus wood (ARANTES , 2008;PROTÁSIO et al, 2012;MORI, 2003;VALE et al, 2007), agreeing with the values found in this study. Fixed carbon is an important information of biomass quality since it is the most resistant portion that remains in biochar after pyrolysis.…”
Section: Thermogravimetric Analysis -Tgasupporting
confidence: 83%
“…Possibly, the high level of minerals in coffee husk (Table 4) contributed to increase ash content. In the literature the ash content is reported to vary from 9 to 13.86% for coffee husk, and from 0.17 to 0.34% in Eucalyptus wood (ARANTES , 2008;PROTÁSIO et al, 2012;MORI, 2003;VALE et al, 2007), agreeing with the values found in this study. Fixed carbon is an important information of biomass quality since it is the most resistant portion that remains in biochar after pyrolysis.…”
Section: Thermogravimetric Analysis -Tgasupporting
confidence: 83%
“…(2011) avaliando o pergaminho do fruto do cafeeiro obtiveram teor de cinzas de 1,46%, inferior ao F3 (4,84%). Enquanto, que Arantes et. al (2008) encontraram valor superior de teor de cinzas de 9,0% para a casca de café carbonizada.…”
Section: Resultados E Discussão Análises Físico-químicasunclassified